037 Subjective sleep and objective cognition in middle-aged and older adults: Does sex matter?. (3rd May 2021) - Curtis, Ashley; Schmiedeler, Anthony; Jagannathan, Sadhika; Connell, Maggie; Atkinson, Angela; Miller, Mary Beth; McCrae, Christina S
Abstract: Introduction: Worse sleep has been linked to cognitive dysfunction in aging populations. There are known sex differences in the prevalence and presentation of both sleep disturbance and cognitive impairment, but research investigating sex differences in the associations between sleep and objective cognition is limited and inconclusive. We examined sex as a moderator of associations between self-reported sleep and objective cognitive performance in middle-aged/older adults. Methods: Sixty-four adults aged 50+ (Mage= 63.8, SD=7.7; 33 men/31 women) who were cognitively healthy (no mild cognitive impairment, dementia or neurological disorders) completed an online survey (via Qualtrics) measuring self-reported sleep (Pittsburgh Sleep Quality Index; PSQI). Participants completed online cognitive tasks (via Inquisit) measuring inhibition (Stroop task; interference reaction time scores), attentional orienting (Posner Endogenous Cueing Task; reaction time difference between invalidly cued and validly cued trials), and working memory (Sternberg task; proportion correct). Multiple regressions examined whether PSQI subscores (sleep quality, sleep duration, sleep efficiency) were independently associated with or interacted with sex in their associations with cognition, controlling for age and education. Results: Sex interacted with sleep quality in the association with endogenous attentional orienting (p=.01, R-squared=.10). Specifically, worse sleep quality was associated with worse attentional orienting in women (B=22.73, SE=9.53, p=.02) but not men (p=.24). Sex interacted with PSQI-sleep duration (p=.03, R-squared=.08) and PSQI-sleep efficiency (p=.03, R-squared=.08) in the association with inhibition performance. Specifically, worse sleep duration (B=235.28, SE=77.51, p=.004) and sleep efficiency (B=211.73, SE=68.70, p=.003) were associated with worse interference scores in men but not women (ps>.05). No variables were associated with working memory. Conclusion: In middle-aged and older adults, sex moderates associations between self-reported sleep and objective cognition, depending on the sleep parameter and cognitive ability assessed. Findings suggest that women are more vulnerable to the effects of poor sleep quality on spatial attention, whereas men are more vulnerable to the effects of shorter sleep duration and worse overall sleep fragmentation on ability to inhibit task-irrelevant stimuli. Future studies should investigate sex-specific associations between sleep and cognition over time in order to better understand the prospective trajectories of these processes during aging. Support (if any):